1999
DOI: 10.1177/009365099026006004
|View full text |Cite
|
Sign up to set email alerts
|

Support for Censorship of Television Violence

Abstract: This study examined predictors of support for censorship of television violence, including third-person effects (the belief that others are more affected by televised violence than oneself) and exposure to specific news stories about the issue. A random sample of 253 residents in a small, Midwestern metropolitan area participated via telephone interviews. The third-person effect for aggression predicted greater support for censorship, but the third-person effect for mean-world perceptions did not. However, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(26 citation statements)
references
References 25 publications
0
24
0
2
Order By: Relevance
“…The majority of these studies support the behavioral hypothesis of the TPE that claims that TPPs may lead to such behavioral consequences as the likelihood to support censorship (Chia, Lu, & McLeod, 2004;Hoffner et al, 1999;Lee & Yang, 1996;Rojas et al, 1996), government regulation of media content (Cohen & Davis, 1991;Price, Tewksbury, & Huang, 1998;Salwen & Driscoll, 1997), evaluations of idealized body images (Choi, Leshner, & Choi, 2008), sexual risk behaviors among at-risk youth (Chapin, 1999), voting intentions (Banning, 2006;Golan, Banning, & Lundy, 2008), and even unexpected phenomenon such as residential mobility (Tsfati & Cohen, 2005a, 2005b.…”
Section: The Tpe Behavioral Componentmentioning
confidence: 61%
See 2 more Smart Citations
“…The majority of these studies support the behavioral hypothesis of the TPE that claims that TPPs may lead to such behavioral consequences as the likelihood to support censorship (Chia, Lu, & McLeod, 2004;Hoffner et al, 1999;Lee & Yang, 1996;Rojas et al, 1996), government regulation of media content (Cohen & Davis, 1991;Price, Tewksbury, & Huang, 1998;Salwen & Driscoll, 1997), evaluations of idealized body images (Choi, Leshner, & Choi, 2008), sexual risk behaviors among at-risk youth (Chapin, 1999), voting intentions (Banning, 2006;Golan, Banning, & Lundy, 2008), and even unexpected phenomenon such as residential mobility (Tsfati & Cohen, 2005a, 2005b.…”
Section: The Tpe Behavioral Componentmentioning
confidence: 61%
“…The behavioral consequences of the TPE have been examined and adequately supported as well, mostly in terms of censorship and restrictions on harmful media messages. These findings have been placed in a broader context by various authors citing real-world implications in social and political realms (Hoffner et al, 1999;Huge, Glynn, & Jeong, 2006).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This second component predicts that people's perceptions of media influence may lead them to react in certain ways in response to their perceptions, and these reactions described as the behavioral component involve cognitive, perceptual, attitudinal, and other responses (Davison, 1983). As showed in Table 1, many studies on the behavioral component of the third-person hypothesis have also been conducted on a wide range of message types Behavior Chapin (1999) Sexual Risk Taking Chia (2008) Behavioral Intention to Sexual Activities Cohen, Mutz, Price, and Gunther (1988) Defamatory Messages Gunther (1995) Censorship Of Pornography David, Morrison, Johnson, and Ross (2002) Body Image Gunther and Storey (2003) Coordination Reactions Delorme, Huh, and Reid (2006) Prescription Drug Hoffner and Buchanan (2002) Censorship of Television Violence Golan, Banning, and Lundy (2005) Candidate Choice Hoffner et al (1999) Censorship of Television Violence Gunther and Thorson (1992) Persuasive Messages in PSA Huh, DeLorme, and Reid (2004b) Prescription Drug Use Gunther (1991;1995) Pornography McLeod, Eveland, & Nathanson (1997) Censorship of Misogynic Music Haridakis and Rubin (2005) Controversial Issues Rojas, Shah, and Faber (1996) Censorship of Television Violence …”
Section: Third-person Perception Hypothesismentioning
confidence: 99%
“…These studies suggested that perceptions and beliefs about the effects of communication are sometimes very influential, which is referred to as "the influence of presumed media influence" (Gunther & Storey, 2003). Additionally, some studies on the behavioral component have shown that the third-person hypothesis is positively relevant to support for media censorship in the form of restrictions on certain types of media messages (e.g., Gunther, 1995;Hoffner et al 1999;Hoffner & Buchanan, 2002;McLeod, Eveland, & Nathanson, 1997;Rojas, Shah, & Faber, 1996;Salwen, 1998;Tsfati & Cohen, 2007;Wu & Koo, 2001). This evidence is particularly confirmed in the case of mediated messages perceived as having potentially "negative consequences," such as negative political advertising and pornography on the Internet.…”
Section: Third-person Perception Hypothesismentioning
confidence: 99%